Consumer Acceptance Level of Natural Coffee Soap Using Cold Process Technology Based on Type of Coffee Roasting - Lestari, Fitri; Wulandari, Sri; Rosalina; Sella, Elia Fahmi; Andini (Agroindustrial Technology Journal, 2023)
Consumer acceptance level testing can help the industry understand what it wants and needs, especially for product development. This study aim to Â analyze the level of consumer acceptance of coffee natural soap produced by the cold process method based on the type of coffee roasting. The research design used was a completely randomized design with one factor (type of coffee roasting) and three treatments (light, medium, and dark). The consumer acceptance level test was carried out by organoleptic testing on 100 Pat Petulai University student respondents using a Likert scale (1-7). The data were analyzed with Kruskal Wallis. For significantly different results, it was continued with the Menn-Whitney test at a 5% level. The attributes of aroma, texture, surface appearance, and overall appearance showed P>0.05, there was no significant difference in the type of coffee roasting for these attributes, the color attribute showed P<0.05, and there was a significant difference in the type of coffee roasting for the color of the coffee soap. The average acceptance level of color attributes is between 4.75-5.14 (either-to Â slighty likely), aroma attributes range from 3.57-3.67 (Slightly unlikely), texture ranges from 4.79-4.92 (either-slightly likely), surface appearance 4.58- 4.67 (either) and overall appearance 4.88-5.08 (either-slightly likely.